2021
DOI: 10.1159/000512893
|View full text |Cite
|
Sign up to set email alerts
|

Active Surveillance for Incidental (cT1a/b) Prostate Cancer: Long-Term Outcomes of the Prospective Noninterventional HAROW Study

Abstract: <b><i>Introduction:</i></b> Optimal treatment for incidental prostate cancer (IPC) after surgical treatment for benign prostate obstruction is still debatable. We report on long-term outcomes of IPC patients managed with active surveillance (AS) in a German multicenter study. <b><i>Methods:</i></b> HAROW (2008–2013) was designed as a noninterventional, prospective, health-service research study for patients with localized prostate cancer (≤cT2), including patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…First, a majority of the landmark studies on AS report data on those who received prostate biopsies (T1c) in response to elevated PSAs or pathological DREs [ 7 , 22 ], but few, if any, studies have addressed the differences in disease progression between T1a/b and T1c tumors. This is all despite the fact that the incidence of incidentally found PCa is relatively high, at between 8 and 15% [ 23 , 24 , 25 ]…”
Section: Discussionmentioning
confidence: 99%
“…First, a majority of the landmark studies on AS report data on those who received prostate biopsies (T1c) in response to elevated PSAs or pathological DREs [ 7 , 22 ], but few, if any, studies have addressed the differences in disease progression between T1a/b and T1c tumors. This is all despite the fact that the incidence of incidentally found PCa is relatively high, at between 8 and 15% [ 23 , 24 , 25 ]…”
Section: Discussionmentioning
confidence: 99%
“…Magistro et al demonstrated that these two factors were not associated with IPCa after HoLEP in 1125 patients who underwent HoLEP. 3 The role of PSA and PSA density to predict IPCa after HoLEP can be controversial.…”
Section: Author Contributionsmentioning
confidence: 99%
“…2 So we often experience cases that cannot be diagnosed with prostate cancer, suspecting them having prostate cancer from biochemical and imaging findings. The prognosis of IPCa, which pathological stage is T1a or T1b, is relatively good, 3 but additional surgery or radiation therapy is sometimes required, affecting the patient's quality of life. 4 Therefore, it is crucial to identify the detection rate and risk factors of IPCa by BPH surgery.…”
mentioning
confidence: 99%
“…Although the level of evidence is limited, the literature suggests that very low prostate-specific antigen (PSA) after BPO surgery (mainly <1 ng/ml), very low PSA density (PSAd) after BPO surgery (0.03 ng/ml/cm 3 ), and the absence of suspicious lesions on multiparametric magnetic resonance imaging (mpMRI) are predictors of the absence of residual tumor [6,7]. If not performed before BPO surgery, mpMRI might be useful for detection of residual suspicious lesions and trigger targeted biopsy to rule out residual csPCa [8].…”
mentioning
confidence: 99%
“…Patients with favorable prognostic factors (initial PSA <10 ng/ml, low PSA and low PSAd after surgery) and only ISUP grade 1 cancer in the resected tissue can be considered at low risk [6]. AS or watchful waiting should be offered on the basis of the individual's life expectancy.…”
mentioning
confidence: 99%